Inhalacijska terapija - Campolunghi, Sanda (Obzornik zdravstvene nege, 1999)
The article presents the role and significance of inhalation therapy in patiens with respiratory diseases, different systems of inhalations therapy, their positive and negative aspects and contains detailed instructions on the use of different inhalers. The article also deals briefly with the history of inhalation therapy, drugs most often used in inhalation therapy arid hygienic and epidemiological problems related to inhalation. Nurse should be adequatelytrained to carry out adequate education of patients - users of such therapy. Only in this way, the effects of the drugs prescribed by the doctor will be optimal.
Keywords: Administration, inhalation; aerosoli; Aerosols; bolezni dihal; inhalacija; inhalatorji; Nebulizers and vaporizers; Respiratory therapy; therapy; zdravljenje